The effect of sampling height on grass pollen concentrations in different urban environments in the Helsinki Metropolitan Area, Finland - Hugg, Timo T. (PLoS One, 2020)
INTRODUCTION: It is important to study potential differences in pollen concentrations between sampling heights because of diverse outdoor and indoor activity of humans (exposure) at different height levels in urban environments. Previous studies have investigated the effect of height on pollen concentrations based on just one or a few sampling points. We studied the effect of sampling height on grass pollen concentrations in several urban environments with different levels of urbanity. METHODS: This study was conducted in the Helsinki Metropolitan Area, Finland, in 2013 during the pollen season of grasses. Pollen grains were monitored in eight different points in the morning and afternoon. Rotorod-type samplers were attached on sampling poles at the heights of 1.5 meters and 4 meters. RESULTS: Grass pollen concentrations were on average higher at the height of 1.5 meters (Helsinki mean 5.24 grains / m(3); Espoo mean 75.71 grains / m(3)) compared to the height of 4 meters (Helsinki mean 3.84 grains / m(3); Espoo mean 37.42 grains / m(3)) with a difference of 1.40 grains / m(3) (95% CI -0.21 to 3.01) in Helsinki, and 38.29 grains / m(3) (7.52 to 69.07) in Espoo, although not always statistically significant. This was detected both in the morning and in the afternoon. However, in the most urban sites the levels were lower at 1.5 meters compared to 4 meters, whereas in the least urban sites the concentrations were higher at 1.5 meters. In linear regression models with interaction terms, the modifying effect of urbanity on concentration-height relation was statistically significant in both cities. The effect of urbanity on pollen concentrations at both heights was stronger in less urban Espoo. CONCLUSIONS: The present study provides evidence that height affects the abundance and distribution of grass pollen in urban environments, but this effect depends on the level of urbanity.